Management of Eco-Tourism Sites: A Case Study of the Ajanta Caves - Ragde, Rajesh; Swant, Madhuri T (Atna Journal of Tourism Studies, 2007)
In the International tourism parlance India is perceived as a Cultural Destination and the foreign tourists visiting India for the first time find it so fascinating that quite a few of them come again and again to enjoy the "Indian Experience". No wonder India is one such destination in the world where international tourists spend maximum days once they arrive in the country. India is replete with heritage resources in the form of art, architecture and archaeology besides other cultural expressions like performing arts, dance, drama, fairs, festivals and the like. These cultural expressions constitute potential recreation resources. These resources, coupled with heritage, contribute to the richness of any landscape which can attract innumerable tourists looking for the "cultural experience". The general conference of UNESCO adopted a resolution in 1972 creating thereby a convention concerning the protection of the world 's cultural and natural heritage. The main objective of this forum was to define the world heritage, enlist sites and monuments from the member countries, the protection of which is the concern of mankind. The convention defined world heritage and drew a list of world heritage which included 378 cultural properties / sites. In India it has identified 28 sites, which are star attractions for intemational and domestic tourist. The paper makes introspection in various managerial aspects focusing mainly on the environmental impacts and problems in conservation and preservation of the World Heritage Site of Ajanta Caves, its paintings and environment in the vicinity of the cave.